Methodology and organisation of scientific research in the field of biology (for foreign students): Test tasks - Sukhomlin, Kateryna B.; Zinchenko, Oleksandr P.; Sukhomlyn, Maryna M.; Zinchenko, Mariia O. (Lesya Ukrainka Volyn National University, 2023)
The publication contains 315 test tasks from different sections of the normative course «Methodology and Organisation of Scientific Research in Biology», provided by the curriculum for Master's degree in 091 «Biology and Biochemistry», answers to them, a list of recommended reading and Internet resources. The tests are intended for intermediate and final control of students' knowledge.
Keywords: science; research; methods; tests; 331.87: 001.891 (076)